A study on the relationship between FDI inflows and corruption: investigation in Muslim world / Ahmad Said Mohamad - Mohamad, Ahmad Said (2016)
This study investigates foreign direct investment linkage between corruption and also towards others determinants such as Gross Domestic product, Political Stability and Trade Openness. The issues of this study is to know and get the clear picture of the volatility of foreign direct investment inflows whether it is depends with other determinants of foreign direct investment based on latest data of information from 2002 until 2014. Besides that, the purpose of this study is to have a clear view on the relationship between the dependent variable of ForeiY1 Direct Investment (FDI) and independent variables of corruption (CPI), Gross Domestic Product (GDP), Political Stability (PS) and Trade Openness (TO). The data observation data are collected for 65 observations of yearly data of each observe variables using Data Steam Online. The data has been analysed by using Eviews 8.0 to do descriptive, unit root test, multiple regression, correlation analysis and test on assumption. The findings shows corruption are negative significant relationship with FDI and for others determinants mentioned, Political Stability have a positive significant relationship with FDI in explaining the linkage of FDI and its determinants. However others variable, Gross Domestic Product and Trade openness was surprisingly insignificant towards FDI which indicate that there no relationship existed among gross domestic product and trade openness towards FDI.